Edukasi Regulasi Keselamatan dan Kesehatan Kerja Konstruksi pada Pekerja Konstruksi di Sumatera Utara - EL- Matury, Herlina Jamaluddin (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
The level of implementation of occupational health and safety is still far from what was expected, even though the workforce as a company asset requires protection to increase productivity to support the company's development. Work accidents in construction result from a lack of compliance with requirements for implementing occupational safety and health (K3), a lack of awareness by companies and workers about the risks that can be borne, and project implementers ignoring occupational safety and health. The use of personal protective equipment and work protective equipment is mandatory for construction workers to protect workers and construction work